2015
DOI: 10.1002/chem.201500121
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Regioselectivity of the Oxidation of Asymmetric Secondary Amines with Singlet Oxygen

Abstract: Aerobic amine oxidation is an attractive and elegant process for the α functionalization of amines. However, there are still several mechanistic uncertainties, particularly the factors governing the regioselectivity of the oxidation of asymmetric secondary amines and the oxidation rates of mixed primary amines. Herein, it is reported that singlet-oxygen-mediated oxidation of 1° and 2° amines is sensitive to the strength of the α-C-H bond and steric factors. Estimation of the relative bond dissociation energy b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 108 publications
2
37
0
1
Order By: Relevance
“…110 As shown in Figure 1, a good linear relationship between the selectivity and the difference in % s character can be established for unsymmetric secondary amines with less bulky substituents (circle dots). The amines with higher differences in % s character gave better selectivity than those with lesser differences, and the oxidative dehydrogenation was preferred to occur at the less hybridized α-CH side (Scheme 34a).…”
Section: Scheme 33 Proposed Photocatalytic Process For the Self-couplmentioning
confidence: 72%
See 1 more Smart Citation
“…110 As shown in Figure 1, a good linear relationship between the selectivity and the difference in % s character can be established for unsymmetric secondary amines with less bulky substituents (circle dots). The amines with higher differences in % s character gave better selectivity than those with lesser differences, and the oxidative dehydrogenation was preferred to occur at the less hybridized α-CH side (Scheme 34a).…”
Section: Scheme 33 Proposed Photocatalytic Process For the Self-couplmentioning
confidence: 72%
“…97 In addition, primary benzylic amines were also suitable for the reaction. It was revealed that the exposure of both (040) and (110) facets of BiVO 4 played important roles in promoting the spatial separation of photogenerated electrons and holes to enhance the catalytic activity. Considering the steric hindrance around the nitrogen atom, the adsorption of bulky N-tert-butyl derivatives on BiVO 4 was unfavorable, and the substrates, therefore, were likely to be oxidized via a direct oxidative dehydrogenation pathway rather than the formation of aldehyde intermediates.…”
Section: Scheme 26 the Mechanism Of Benzylamines Oxidation On Agi/tntmentioning
confidence: 99%
“…Recently, the method was extended to allow for the preparation unnatural amino acids 193 and selective crosscondensation of amines. 194 Scheme 18. Continuous-flow aerobic oxidative cyanation of primary and secondary amines using singlet oxygen.…”
Section: Homogeneous Catalysismentioning
confidence: 99%
“…Stimulated by the ground-breaking works of the Seeberger [4142 47,5051], Booker-Milburn [5253], and Noël [34,5455] groups in recent years, we therefore decided to develop our own home-made flow reactor for photooxidations of organic molecules but also envisaged its general applicability to other challenging processes with the ternary “reagent” combinations liquid/gas/light. With the objective of constructing a robust and versatile flow reactor, we set out to explore and test commercially available parts.…”
Section: Resultsmentioning
confidence: 99%
“…Under irradiation in the presence of a sensitizer, singlet oxygen can easily be generated from the triplet ground state. Several applications of such photooxidations to chemical synthesis have been reported [7173], in recent years most effectively under microflow conditions [4142 5051 7475]. …”
Section: Resultsmentioning
confidence: 99%